Genetic polymorphism of the serine rich antigen N-terminal region in Plasmodium falciparum field isolates from Brazil - Riccio, Evelyn Kety Pratt (2005)
In this work we investigated the frequency of polymorphism in exon II of the gene encoding most of the amino-terminal region of the serine rich antigen (SERA) in Plasmodium falciparum field samples. The blood samples were colleted from P. falciparum infected individuals in three areas of the Brazilian Amazon. Two fragments have been characterized by polymerase chain reaction: one of 175 bp corresponding to the repeat region with 5 octamer units and one other of 199 bp related to the 6 repeat octamer units of SERA protein. The 199 bp fragment was the predominant one in all the studied areas. The higher frequency of this fragment has not been described before and could be explained by an immunological selection of the plasmodial population in the infected individuals under study. Since repeat motifs in the amino-terminal region of SERA contain epitopes recognized by parasite-inhibitor antibodies, data reported here suggest that the analysis of the polymorphism of P. falciparum isolates in different geographical areas is a preliminary stage before the final drawing of an universal vaccine against malaria can be reached.